Phytoplankton community structure changes in Thi Nai lagoon (South - Central Vietnam) from 2004 to 2020 - Duyen, Huynh Thi Ngoc; Hue, Tran Thi Minh; Van, Tran Thi La; Luom, Phan Tuan; Lam, Nguyen Ngoc; Hai, Doan Nhu (Academia Journal of Biology, 2021)
Phytoplankton species composition, abundance, biodiversity indices and their influence by environmental conditions were examined in Thi Nai lagoon using data from four surveys in 2004, 2008, 2009 and 2020. A total of 367 taxa of phytoplankton belonging to ten groups was recorded, of which diatoms were dominant with over 60% of the total species. In Thi Nai lagoon, the number of phytoplankton species decreased from the upper lagoon (283 taxa) to the lagoon mouth area (224) and was lowest in river stations (139). The species number was much lower in the rainy season (<95 species) and increased from 2004 to 2020. Among the biodiversity indices, Shannon, ∆, s∆+, Λ+ and sФ+ were lower in the rainy season, whereas ∆*, ∆+ and Ф+ had lower values in the dry season. For long-term analysis, the differences were especially significant at upper and lower lagoon for ∆, ∆*, ∆+, s∆+ and sФ+. In the dry season, the mean density of phytoplankton was lower at the river stations and upper lagoon, but higher at the lower lagoon and the lagoon mouth area. There was a clear difference of species assemblages between the two seasons with average dissimilarities in each area ranging from 94.16% to 95.57%. During 2004–2020, the difference in ratios between the main phytoplankton groups were small over years but there was a complete change in dominance of particular species, assemblage dissimilarities were from 73.4 to 77.9, greatest between 2009 and 2020. The lagoon was low in biodiversity for the whole investigated time indicated by taxonomic index ∆+. Among biodiversity indices, species richness (S), taxonomic indices (∆*, s∆+), and phylogenetic indices (Ф+, sФ+) were more sensitive to the changes of the aquatic environment than other traditional indices.